A rationale and framework for seeking remote electronic or phone consent approval in endovascular stroke trials – special relevance in the COVID-19 environment and beyond. (7th May 2020) - Rai, Ansaar T; Frei, Donald
Abstract : Background: Enrollment in time-sensitive endovascular stroke trials can be challenging because of an inability to consent a debilitated patient. Often the legally authorized representative is not on site. Remote consent procedures in the US are inconsistent with the majority of sites shunning these approaches. The current pandemic with visitor restrictions highlights the need for enhancing these options. Methods: Remote electronic and phone consent procedures specifically for endovascular stroke trials from two comprehensive stroke centers (CSC) are presented. An overview of the genesis of informed consent procedures in the US is also included. Results: The two CSCs identified as Institution-1 and Institution-2 are large tertiary systems. Institution-1 is a non-profit university-affiliated academic medical center in rural geography. Institution-2 is an HCA hospital in an urban environment. Both serve patients through a spoke-and-hub network, have participated in multiple randomized endovascular stroke trials, and have successfully used these remote options for enrollment. A tiered approach is employed at both institutions with an emphasis on obtaining informed consent in person and resorting to alternatives methods when efforts to that are unsuccessful. A rationale for electronic and phone consent is included, followed by step-by-step illustration of the process at each institution. Conclusion: Two examples of remote electronic or phone consent procedures from institutions in different geographic environments and organization structures demonstrate that these options can be successfully used for enrollment in stroke trials. The current pandemic highlights the need to enhance these approaches while maintaining appropriate adherence to ethical and legal frameworks.